The Application of Restorative Justice in Corruption Crimes - Sofyan Saleh; Jantje Tjiptabudy; Sherly Adam (International Journal of Social Service and Research, 2026)
Corruption is an extraordinary crime with systemic impacts on state finances, government stability, and public trust, requiring a comprehensive legal approach to address it effectively. Meanwhile, the concept of restorative justice has increasingly developed within modern criminal justice systems as an alternative to the retributive justice paradigm, which primarily emphasizes punishment rather than repairing harm caused by criminal acts. This study aimed to examine the legal framework governing the application of restorative justice in corruption cases in Indonesia and analyze the extent to which this concept could be implemented within the practice of criminal law enforcement against corruption. This study employed a normative legal research method using statutory, conceptual, and case approaches. The legal materials consisted of primary, secondary, and tertiary legal sources collected through literature studies and analyzed qualitatively. The findings showed that the regulation of restorative justice in corruption cases had not been explicitly established under Law Number 31 of 1999 concerning the Eradication of Corruption Crimes, as amended by Law Number 20 of 2001, and remained limited in scope. Its application was primarily reflected through mechanisms for recovering state losses rather than functioning as a basis for terminating investigations, prosecutions, or eliminating criminal liability. In practice, restorative justice in corruption cases was oriented toward the recovery of state losses, payment of replacement money (uang pengganti), and judicial consideration of the defendant’s good faith, without eliminating criminal accountability, as affirmed in Article 4 of the Anti-Corruption Law. Therefore, clearer regulatory reform is required to enable the proportional application of restorative justice without undermining the deterrent effect of Indonesia’s efforts to combat corruption.